Weather notification system using GSM - Shia, Hui Ching (2013)
Weather Notification System is web site systems which use the GSM modem send SMS (Short Message Service) to customer/client for notify the weather information. By using this system customer would be able to get the notify message/information more easily. Before this, customer only can get the notification by manually. They need to request the notification message every time when they hope to know about the weather condition. But, with using this system, the task become more easily. When newweather information is entry or recorded into the system, the system will send the notify message to related customer. Hence, customer only needs to request to the system one time. Then, the system will update the notify message every time without waiting for customer asking for.The main advantage of this system is that it help customer get the notify message more easily. It is also helpful for staff to manage the web site.